Pengaruh Pertumbuhan Ekonomi Daerah, Pendapatan Asli Daerah (PAD), Dana Alokasi Umum (DAU), dan Dana Alokasi Khusus terhadap Belanja Daerah pada Kabupaten/Kota di Provinsi Sumatera Utara - Salsa Okdania Lubis; Dito Aditia Darma Nasution (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to examine the influence of regional economic growth, original regional income, general allocation funds, special allocation funds on regional expenditure. The population in this study used 33 regencies/cities in North Sumatra with observations for 4 years from 2018 - 2021. The approach used in this research was an associative approach and the data analysis technique used was Multiple Linear Regression Analysis. The sampling method used in this research is the Census. This research was processed using SPSS Version 23. The results of this research show that Regional Economic Growth has no effect on regional expenditure, Regional Original Income, General Allocation Funds, Special Allocation Funds have a positive effect on Regional Expenditure. Regional Economic Growth, Original Regional Income, General Allocation Funds, Special Allocation Funds Simultaneously Influence Regional Expenditures.